REBRANDING INDUSTRI PERBANKAN: INVESTIGASI PERAN RELIGIUSITAS DALAM MEMPENGARUHI PERSEPSI KONSUMEN - Dahlawy, Rifyal (IAIN Langsa, 2022)
This study aims to examine the role of rebranding and corporate image on customer-based brand equity (CBBE), as well as the moderating role of the religiosity variable in the relationship between rebranding and corporate image on CBBE. This research is a survey using a questionnaire as a data collection tool. The sampling method used is convenience sampling with 100 respondents from banking customers in Langsa City as the sample. For the data analysis methods, using multiple linear regression testing (t-test, F-test, and R2). To test the effect of moderating variables, Moderated Regression Analysis (MRA) technique is used. The results revealed that rebranding proved to have a positive and significant effect on CBBE, as well as the effect of brand image on CBBE. To examine the moderating effect of the religiosity variable, it is only proven that there is a moderating effect of religiosity on the relationship between brand image and CBBE.